Reserve Accumulation in Asia and Its Impact on the Economic and Monetary Union and the Euro - Bogołębska, Joanna (Akumulacja rezerw walutowych w Azji i jej wpływ na funkcjonowanie Unii Gospodarczej i Walutowej (UGW) oraz euro, 2010)
The accumulation of reserves is an essential clement of economic policies pursued within Asian countries, which influences the external imbalances and the global economy. For the EMU, accumulation and exchange rate policy of Asian countries has adverse effects, as it influences the euro and competitiveness of the European manufacturing sector. In general - the lesser extent of exchange rate flexibility, the bigger appreciating pressure on the euro. For the European Central Bank, it generates dilemma on the rationality and effectiveness of intervention policy. Another channel, through which Asian reserve policy influences the euro is the currency structure of reserve portfolio, and the extent to which the euro substitutes the dollar as reserve currency. The conclusion is, that it may make sense to distinguish between motives of reserve accumulation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 112-120
Keywords: reserve accumulation; exchange rate policy; global imbalances